2003
DOI: 10.1046/j.1365-2761.2003.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced total hardness of fresh water enhances the efficacy of bathing as a treatment for amoebic gill disease in Atlantic salmon, Salmo salar L.

Abstract: The current treatment for amoebic gill disease (AGD)-affected Atlantic salmon involves bathing sea-caged fish in fresh water, often sourced from local dams, for 3-4 h. In both a small-scale laboratory and an on-farm field experiment, the effects of water hardness on the efficacy of freshwater bathing were assessed. Results showed that soft fresh water (19.3-37.4 mg L(-1) CaCO3), whether it be naturally soft city mains water or artificially softened dam water, was more efficacious at alleviating AGD in affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 14 publications
1
43
0
Order By: Relevance
“…Comparatively, field outbreaks of clinical AGD on commercial salmon farms exhibit much less severe infection rates than laboratory-induced infections. Roberts & Powell (2003b) showed that AGD-affected fish in a field experiment on a commercial salmon farm had 5% of gill filaments with an AGD lesion, which coincided with a gross gill score that initiated freshwater bathing. Fish returned to a similar level of infection 8 wk post-bath.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Comparatively, field outbreaks of clinical AGD on commercial salmon farms exhibit much less severe infection rates than laboratory-induced infections. Roberts & Powell (2003b) showed that AGD-affected fish in a field experiment on a commercial salmon farm had 5% of gill filaments with an AGD lesion, which coincided with a gross gill score that initiated freshwater bathing. Fish returned to a similar level of infection 8 wk post-bath.…”
Section: Discussionmentioning
confidence: 98%
“…Briefly, AGD had been maintained in this tank for several months, with introduced fish exhibiting gross signs of AGD within 3 d of cohabitation. The presence of Neoparamoeba pemaquidensis, the putative agent of AGD, was routinely confirmed using a modified indirect fluorescent antibody test (Roberts & Powell 2003b), PCR (Wong et al 2004), immunohistochemistry (Bridle et al 2003 and by visually identifying parasomes within isolated gill amoebae (Morrison et al 2004). All fish were fed to satiation daily with non-medicated pellets, and further lethally sampled 3 and 5 d into their cohabitation with AGD-affected fish.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations